Executive Compensation, Corporate Governance and Financial Reporting Quality: Evidence from listed firms in Nigeria - Titilope Esther Olorede; Segun Abogun; Johnson Kolawole Olowookere (Istanbul Management Journal)
In many emerging economies with less efficient market systems like Nigeria, investors tend to rely on financial reports for decision-making. Managerial opportunistic behavior is associated with the need to achieve performance-based remuneration targets. However, corporate governance mechanisms are established to monitor managerial affairs which are believed to curb such behaviors. Hence, this study assesses the influence of executive compensation on the quality of financial reports with an interactive effect of corporate governance in Nigerian listed firms. The population of the study comprised all listed companies on the Nigerian Exchange Group (NGX) from which 74 firms were selected. Executive compensation was proxied with the chief executive officer’s total remuneration, and the corporate governance index was adopted as a measure of corporate governance. The discretionary accruals from the modified Jones model by Kothari, Leone, and Wasley (2005), and the accruals of Dechow and Dichev (2002) proxied for financial reporting quality. The estimation results showed that the interactive effect of executive compensation and corporate governance has a significant and negative influence on discretionary accruals, which indicates a positive relationship with reporting quality.